Production of pepper seedlings with different doses of organic compounds in substrate - Manzani Lisboa, Lucas Aparecido [UNESP]; Cardoso, Alan dos Santos; Pirola Narimatsu, Karem Cristine; Oliveira Crispim, Nubia Priscila de; Conde de Almeida, Pedro Henrique de; Amaral Sacco, Hiago Augusto; Pereira, Leandro Barradas; Oliveira Dias, Carlos Eduardo de (Univ Federal Mato Grosso, 2020)
One of the main responsible attributes for the good quality of seedlings is its cultivation in substrates with a good drainage and nutrients availability. This work aimed to study the production of pepper seedlings with different doses of organic compounds in substrate. The experiment was carried out in August, 2018, at Educational Foundation of Andradina, in Andradina, Sao Paulo State, Brazil. The experimental design was completely randomized, in a 2x5 factorial scheme, with two organic substrates: peaty exhausted compound (EC) and coconut fiber compound (CC), in five different concentrations: null %; 25%; 50%; 75% and 100%, with five repetitions, in total of fifty plots. The increase in the concentration of organic compounds in production of pepper seedlings promoted a greater development. It is recommended using 70% of peaty exhausted in the composition of substrate to the production of pepper seedlings and using 100% of coconut fiber in the composition of the substrate to the production of pepper seedlings.
Keywords: Capsicum annuum L.; nutrition of plants; vegetables